Cochlear implant telemedicine: Remote fitting based on psychoacoustic self-tests and artificial intelligence. (2nd September 2020) - Meeuws, Matthias; Pascoal, David; Janssens de Varebeke, Sebastien; De Ceulaer, Geert; Govaerts, Paul J.
Abstract : Objective: This study aims to assess the feasibility of autonomous cochlear implant (CI) fitting by adult CI recipients based on psychoacoustic self-testing and artificial intelligence (AI). Design: A feasibility study was performed on six adult CI recipients implanted with a Nucleus device. Two weeks after processor activation in the clinic, a 'self-fitting' session was organized in a supervised simulated home environment. The CI recipient performed pure tone audiometry and spectral discrimination tests as self-tests. The AI application FOX analysed the results and recommended a new map. The participants filled out a questionnaire and were tested again after 2 months of take-home experience. Results: Four out of six patients performed the self-tests without any help from the audiologist and four were fitted by FOX without any manual intervention. All patients were comfortable with the concept of self-testing and automated fitting. Patients acknowledged that at this stage the remote supervision of an audiologist remains essential. Conclusions: The study showed that audiological self-assessment and remote CI fitting with AI under the supervision of an audiologist is feasible, at least in a number of CI recipients. Currently, there are still some technical and regulatory challenges to be addressed before this can become routine practice.